Why are individuals likely to change to sustainable modes of transport like carsharing and electric vehicles? An empirical analysis - Elisabeth Dütschke; Anja Peters (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2017)
Replacing conventional vehicles by electric vehicles (EVs) and increasing the use of carsharing are two strategies to reduce the environmental impact of car driving. However such a societal transition towards the use of more sustainable modes of transport will strongly depend on citizens' willingness to support this process. For this reason, this paper tries to identify factors which are related to the individual likelihood to change to more sustainable modes of transport. It draws on an adapted version of Rogers' diffusion of innovation model (DOI) and earlier work by the authors. It presents new findings from an online survey (n=1548) in one of Germany's show case regions for electric vehicles. Findings point out that relatively small shares of respondents already use these sustainable modes of transport (.6% for EV ownership and 5.3% for carsharing). Similarly, the shares of individuals who are very likely to use them in the near future (4.2% and 4.6% respectively) are also small. Much more individuals are interested in EVs (55.9%) than in carsharing (21.2%), and large groups are not interested (37.7% for EVs, 68.9% for carsharing). There are several significant sociodemographic differences between the respective four adoption groups. Furthermore, consistently, evluations are significantly more positive the higher the likeliness of adoption across groups. Based on regression models, it turns out that perceived compatibility with daily life is the most important factor influencing the attitudes towards EVs or carsharing across all groups.
urn:nbn:de:0011-n-4562204
Keywords: 330; Electric vehicles; Carsharing; Adoption; Diffusion of Innovation